Primi sondaggi sul testimone J del volgarizzamento catalano della Consolatio Philosophiae. - CONCINA, CHIARA (Scripta, 2015)
The history of Boethius's De consolatione philosophiae Catalan translation is particularly complex for what concerns its manuscript tradition as well as for the textual differences that can be found in the exstant versions of it. The lost original version of this vernacular translation, written around the years 1358-1362 by the Dominican friar Pere Saplana, is preserved in two different versions. The first one (α) is anonymous, and has survived in its complete form in a Castilian translation and in a Catalan fragment. The second (β) is transmitted by a large number of witnesses and is the result of a revision of Saplana's text made around 1390 by the Dominican Antoni Ginebreda. One of the two manuscripts containing this translation preserved in the Arxiu Comarcal de la Segarra of Cervera (designed as J) was recently mentioned as the possible bearer of a version very similar to a, considered the closest to Saplana's original text. The paper offers a first analysis of the structure and the readings of the text of J, comparing them to the versions transmitted by α and β.